(untitled) (International Journal of Engineering Management Science, 2022)
The preparation of bis-thiazolidinones has been achieved by a one-pot condensation reaction of araldehydes, ethylenediamine and thioglycolic acid in the presence of nano-CuCr2O4 nanoparticles under reflux conditions in toluene. This method provides several advantages including easy workup, excellent yields, short reaction times, reusability of the catalyst and low catalyst loading